Lexicogenic matrices and institutional roles of U.S. military jargon - Anthony Saber (Lexis: Journal in English Lexicology, 2018)
Specialized lexis used by American military personnel includes an official technolect, technical nomenclatures, tactical codes, as well as an abundant, diversified jargon. The latter is spontaneously created by the members of military units, and relies on several lexicogenic matrices, which we attempt to classify in this study by reformulating available descriptions of lexicogenic mechanisms. Metaphors and abbreviations account for a significant proportion of the 190 items in our dataset. An analysis of the institutional roles played by U.S. military jargon was also carried out: alongside bonding, humor and encryption, this lexical material also serves to recount implicit narratives, express negative stance about the military, and formulate stereotypes about the constraints of military life. Building “role diagrams” allows to visualize the balance between these six roles for an individual lexical item.